The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1292/jvms.11-0251
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Comparison of Applanation Tonometry and Rebound Tonometry in Dogs

Abstract: ABSTRACT. Intraocular pressure (IOP) evaluated by applanation tonometry via TONO-PEN XL (TP), and rebound tonometry via TonoVet (TV) were compared in enucleated canine eyes with varied pressure of the anterior chamber (AC) and in clinical cases. TV measured IOP values were lower than IOP measurements of TP in the enucleated eyes with 5-10 mmHg of AC (P<0.0001), though there was no significant difference in IOP values obtained with TP and TV on the pressure ranges of 15-20 mmHg. However, TP detected IOP values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 17 publications
4
31
1
Order By: Relevance
“…13 IOP readings in adult dogs, obtained using the same type of rebound tonometer as applied in the current study, ranged between 9.16 AE 3.47 mmHg and 14.2 AE 4.5 mmHg. [22][23][24] In the present study, the initial IOP of 5.6 AE 2.7 mmHg at 2 weeks of age was below or within the lowest reported reference range for IOP in adult dogs. IOP increased significantly to 12.6 AE 1.8 mmHg at 6 weeks of age, which is well within the reported reference ranges for adult dogs.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…13 IOP readings in adult dogs, obtained using the same type of rebound tonometer as applied in the current study, ranged between 9.16 AE 3.47 mmHg and 14.2 AE 4.5 mmHg. [22][23][24] In the present study, the initial IOP of 5.6 AE 2.7 mmHg at 2 weeks of age was below or within the lowest reported reference range for IOP in adult dogs. IOP increased significantly to 12.6 AE 1.8 mmHg at 6 weeks of age, which is well within the reported reference ranges for adult dogs.…”
Section: Discussioncontrasting
confidence: 49%
“…The youngest dogs in which IOP was described were 6 weeks of age, and IOP at that age did not differ significantly from IOP one year later . IOP readings in adult dogs, obtained using the same type of rebound tonometer as applied in the current study, ranged between 9.16 ± 3.47 mmHg and 14.2 ± 4.5 mmHg . In the present study, the initial IOP of 5.6 ± 2.7 mmHg at 2 weeks of age was below or within the lowest reported reference range for IOP in adult dogs.…”
Section: Discussionsupporting
confidence: 46%
“…Rebound tonometry has shown a strong linear relationship when compared with results obtained with manometry in enucleated dog eyes (Knollinger et al 2005 ). A separate study using manometry reported that rebound tonometry was reliable in hypertensive eyes (Nagata et al 2011 ). Rebound tonometry gives higher readings than applanation tonometry in dogs with acute glaucoma and an IOP that is >25 mmHg (Slack et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 ] Previous studies have shown that the Tono-Pen readings were not significantly different from the Tonovet readings for normotensive eyes. [ 36 , 37 ] Since all IOPs in our previous study were within the range of 10–18 mmHg, these IOP data were combined in the analyses without further conversion. Tonometry was performed on most of the dogs throughout their lifespans ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%